2010
DOI: 10.1007/s00244-010-9483-8
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Accumulation in Lake Sediments, Fish (Oreochromis niloticus and Serranochromis thumbergi), and Crayfish (Cherax quadricarinatus) in Lake Itezhi-tezhi and Lake Kariba, Zambia

Abstract: Heavy metal accumulation in lake sediments, fish (Oreochromis niloticus and Serranochromis thumbergi) and crayfish (Cherax quadricarinatus) in Lake Itezhi-tezhi and Lake Kariba, AbstractWe measured the level of heavy metal accumulation in lake sediments, herbivorous (Oreochromis niloticus) and carnivorous (Serranochromis thumbergi) fish, and crayfish (Cherax quadricarinatus) from Lake Itezhi-tezhi (ITT) and Lake Kariba. We used atomic absorption spectrophotometry (AAS) to quantify the levels of 7 heavy metals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 39 publications
6
28
1
2
Order By: Relevance
“…Generally speaking, 52 Cr displayed correlations with a greater number of metals compared with 53 Cr. Male specimens' Cr-Ni correlations in hepatopancreas is similar to the results of Nakayama et al (liver results) performed on Nile tilapia (Oreochromis niloticus), whereas Cr-Pb results are dissimilar (Nakayama et al 2010).…”
Section: Resultssupporting
confidence: 87%
“…Generally speaking, 52 Cr displayed correlations with a greater number of metals compared with 53 Cr. Male specimens' Cr-Ni correlations in hepatopancreas is similar to the results of Nakayama et al (liver results) performed on Nile tilapia (Oreochromis niloticus), whereas Cr-Pb results are dissimilar (Nakayama et al 2010).…”
Section: Resultssupporting
confidence: 87%
“…1). In agreement with previous studies that reported high concentrations of Cu in water and sediment around mining areas in the Copperbelt region (Choongo et al, 2005;Ikenaka et al, 2010;Mwase et al, 1998;Norrgren et al, 2000), we observed that Cu pollution occurred in the northern part of the lake, probably from the Copperbelt mining area, where Cu wastes passed through the Kafue River and reached Lake ITT located in the Kafue National Park. On the contrary, Cd and Hg distribution patterns were different from those of Cu.…”
Section: Resultssupporting
confidence: 93%
“…Approximately 40% of the sediments showed higher concentrations of Cu compared with the benchmark value, while Cd and Hg concentrations were below the benchmark value (Forstner, 1981;Yabe et al, 2010). Moreover, current results in Lake ITT sediments showed higher concentrations of Cu compared with the Cu levels in sediments from Lake Kariba in Zambia (6-56 mg/kg dry-wt, Student's t-test, (Nakayama et al, 2010)). According to GIS analysis, relatively higher concentrations of Cu were recorded in the sediment from the northern part of the lake, suggesting that Cu wastes actually reached Lake ITT (Fig.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Metals were extracted from the soil samples using a method modified from our previous study (Nakayama et al, 2010). Briefly, 1 g of each soil sample was placed in a 200 mL flask.…”
Section: Extraction and Measurement Of Metalsmentioning
confidence: 99%